Hydrologic Response of a forested Mountain Watershed to Thinning: a Case Study - Subba Rao, B. K.; Ramola, B. C.; Sharda, V. N. (Indian Forester, 1985)
The paper deals with the effect of thinning (20%) on peak flow and fort-nightly runoff in a forested mountainous watershed near Dehra Dun, U.P. India. It has been found that the peak rate of flow increased by 8.6% in the first year (significant at 5% level) but the effect was insignificant in the second year after thinning. There was no significant effect on the total volume of fort-nightly runoff either in the first year or in the second year after thinning.